TUNGAU DEBU RUMAH YANG DITEMUKAN DI KELURAHAN PERKAMIL KECAMATAN PAAL 2 KOTA MANADO - De Breving, Regina F. R. (e-Biomedik, 2013)
Abstract: In house dust are a lot of house dust mites that found in damp houses, cotton mattress, pillows, bolsters, and other home furnishings. Sources of dust containing house dust mites are most in the bedroom especially cotton mattress. Data from distric health centers Paal 2 found that there are many people who suffer from asthma and allergic diseases, coupled with the humid air in Manado City to allow the development of house dust mites in the area. The purpose of this research is to determine the species and density of house dust mites in urban Perkamil Paal 2 districts Manado city. This research method is descriptive survey to obtain data on the species and density of house dust mites by simple random sampling method. The results found 5 species of house dust mites are Dermatophagoides spp, Acarus spp, Glycyphagus destructor, Tarsonemus spp and Cheyletus spp in bedrooms and living room. House dust mite densities obtained an average of 2,33 in bedroom and 2,07 in living room. The conclusion is house dust mite Dermatophagoides spp most commonly found in bedrooms and living room. Keywords: species, density, house dust mite Abstrak: Dalam debu rumah terdapat banyak tungau debu rumah yang ditemukan pada rumah yang lembab, kasur kapuk, bantal, guling serta perabot rumah yang lain. Sumber debu yang mengandung tungau debu rumah terbanyak adalah debu kamar tidur terutama debu di kasur kapuk. Dari data Puskesmas Kecamatan Paal 2 didapatkan bahwa masih banyak masyarakat yang menderita asma dan penyakit alergi, ditambah lagi dengan udara Kota Manado yang lembab sehingga memungkinkan terjadinya perkembangan tungau debu rumah di daerah tersebut. Tujuan penelitian ini untuk mengetahui jenis dan kepadatan tungau debu rumah di Kelurahan Perkamil Kecamatan Paal 2 Kota Manado. Metode penelitian ini secara survei deskriptif untuk mendapatkan data tentang jenis dan kepadatan tungau debu rumah dengan metode simple random sampling. Hasil yang didapat ditemukan 5 jenis tungau debu rumah yaitu Dermatophagoides spp, Acarus spp, Glycyphagus destructor, Tarsonemus spp dan Cheyletus spp di ruang tidur dan ruang tamu. Kepadatan tungau debu rumah didapatkan rata-rata 2,33 di ruang tidur dan 2,07 di ruang tamu. Kesimpulan yang diambil yaitu tungau debu rumah Dermatophagoides spp paling banyak ditemukan di ruang tidur maupun ruang tamu. Kata kunci: jenis, kepadatan, tungau debu rumah